2022
DOI: 10.15244/pjoes/155051
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Factors Controlling Manganese Concentrations in the Leaves of Silver Birch (<i>Betula pendula</i> Roth) in Relation to Recent Acidification of Mountain Forest Soils

Abstract: Manganese concentrations in silver birch leaves were studied in the Ore Mountains and several reference localities in Czechia, both mountainous (up to 950 m MSL) and lowland (ca. 300 m MSL). The studied mountainous areas have been seriously damaged by acid rains in the last decades and forests there have still not recovered from that crisis. The aim of this study was to identify the major controls on the foliar Mn concentration variability, which was more than one order of magnitude, from 200 mg kg -1 (10th pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…Soil acidification enhances Mn uptake by plants through two primary effects: (i) leaching of the nutrient elements calcium (Ca 2+ ) and magnesium (Mg 2+ ) from the soil, leading to their insufficiency in plants, and (ii) mobilisation of Mn species such as Mn 2+ in the soils (Kazda and Zvacek 1989 ; Marschner 1991 ; Heal 2001 ; Reimann et al 2007a ; Begley-Miller et al 2019 ). These processes that lead to high Mn FECs have been found for certain smaller regions and tree species; however, the interpretation of Mn FEC datasets during these preceding studies has thus far been equivocal (Hrdlička and Kula 2004 ; Reimann et al 2007a ; Bílková et al 2023 ), whereas certain studies have found elevated Mn FECs associated with low concentrations of certain nutrients, such as Ca, Mg, and/or phosphorus (P) (Kogelmann and Sharpe 2006 ; Reimann et al 2007a ; Gransee and Führs 2013 ; Lambers et al 2015 , 2021 ; Gilliam et al 2018 ; Zemunik et al 2020 ; De Oliveira and de Andrade 2021 ; Roth et al 2022 ). Lambers et al ( 2015 , 2021 ) interpreted excess Mn FECs as resulting from an enhanced exudation of organic acids.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Soil acidification enhances Mn uptake by plants through two primary effects: (i) leaching of the nutrient elements calcium (Ca 2+ ) and magnesium (Mg 2+ ) from the soil, leading to their insufficiency in plants, and (ii) mobilisation of Mn species such as Mn 2+ in the soils (Kazda and Zvacek 1989 ; Marschner 1991 ; Heal 2001 ; Reimann et al 2007a ; Begley-Miller et al 2019 ). These processes that lead to high Mn FECs have been found for certain smaller regions and tree species; however, the interpretation of Mn FEC datasets during these preceding studies has thus far been equivocal (Hrdlička and Kula 2004 ; Reimann et al 2007a ; Bílková et al 2023 ), whereas certain studies have found elevated Mn FECs associated with low concentrations of certain nutrients, such as Ca, Mg, and/or phosphorus (P) (Kogelmann and Sharpe 2006 ; Reimann et al 2007a ; Gransee and Führs 2013 ; Lambers et al 2015 , 2021 ; Gilliam et al 2018 ; Zemunik et al 2020 ; De Oliveira and de Andrade 2021 ; Roth et al 2022 ). Lambers et al ( 2015 , 2021 ) interpreted excess Mn FECs as resulting from an enhanced exudation of organic acids.…”
Section: Introductionmentioning
confidence: 99%
“…The FECs of nutrients are regulated by homeostasis within relatively narrow ranges and are required to produce all essential metalloenzymes at concentrations needed for plant health (White and Brown 2010 ). In contrast, the variability of Mn FECs is considerably larger (Reimann et al 2001 , 2007a ; Gilliam et al 2018 ; Zemunik et al 2020 ; Araminienė et al 2021 ; Kalliola et al 2021 ; Bílková et al 2023 ), ranging from essential concentrations sufficient for their health (in an order of 10 mg kg −1 ; White and Brown 2010 ; Lambers et al 2015 ) up to 10,000 mg kg −1 in certain hyperaccumulating plants (Lambers et al 2015 ). Most common tree species growing in temperate and boreal forests, such as Norway spruce or European beech, typically show Mn FECs in the order of hundreds to a few thousand mg kg −1 (Reimann et al 2001 ; Kogelmann and Sharpe 2006 ; Houle et al 2007 ; Reimann et al 2007a ; Araminienė et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations